STUDY ON THE PROCESSING OF BISCUITS WITH THE ADDITION OF SNAKE HEAD (Channa striata ) FISH PROTEIN CONCENTRATE - Reko Putra Nando; Suparmi '; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study was to determine the amount of protein added and to seek the best formulations on biscuits which added with snake head fish (Channa striata) protein concentrate. The method used was experimental method by conducting experiments on the processing of biscuits treated with adding snake head fish protein concentrate at concentration of 0 %, 5 % , 10 % and 15 % based on the wheat flour used. Parameter used were sensory evaluation, includingJOM: OKTOBER 2015appearance, taste, texture and odor by using scoring test on 25 semi-trained panelists and the content of protein, moisture, fat, and ash. The results showed that the addition of snake head fish protein concentrate was increasing the protein content of the biscuit (4.02 %, 9.70 %, 16.50 % and 22.23 % respectively). The best formulation was biscuits with the addition of snake head fish protein concentrate 10 % (K2) accepted by consumers, with a highest content of protein 16.50 %, moisture 1.64%, ash 1.49 % and fat 21.37 %.Keywords :Biscuit, Channa striata, Fish Concentrate Protein,